Analysis of a Substructure Part of Metro Structure as Per Live Data Using Analysis Tool - Raushan Kumar; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
A metro system is a railway transport system in an urban area with a high capacity, frequency and the grade separation from other traffic. The Metro System is used in cities, agglomerations, and metropolitan areas to transport large numbers of people. An elevated metro system is a more preferred type of metro system due to ease of construction and also it makes urban areas more accessible without any construction difficulty. An elevated metro system has two major elements: a pier and box girder. The present study focuses on two major elements, pier and box girder, of an elevated metro structural system. The parametric study on behaviour of box girder bridges showed that, as curvature decreases, responses such as longitudinal stresses at the top and bottom, shear, torsion, moment and deflection decreases for three types of box girder bridges and it shows not much variation for fundamental frequency of three types of box girder bridges due to the constant span length. It is observed that as the span length increases, longitudinal stresses at the top and bottom, shear, torsion, moment and deflection increases for three types of box girder bridges. As the span length increases, fundamental frequency decreases for three types of box girder bridges. Also, it is noted that as the span length to the radius of curvature ratio increases responses parameter longitudinal stresses at the top and bottom, shear, torsion, moment and deflection are increased for three types of box girder bridges. As the span length to the radius of curvature ratio increases, fundamental frequency decreases for three types of box girder bridges.